The Characteristic and Thermodynamics/Kinetics of Martensitic Transformation in Fe50Mn30Co10Cr10 High‐Entropy Alloy during Deformation/Heat Treatment. Issue 3 (5th December 2019) - Yang, Shuangjun; Yang, Yang; Wang, Haimin
Abstract : The characteristic of martensitic transformation in the Fe50 Mn30 Co10 Cr10 high‐entropy alloy during deformation/heat treatment is analyzed with optical microscopy (OM) and X‐ray diffraction (XRD). The mechanism of martensitic transformation is first quantitatively analyzed based on Olson–Cohen thermodynamics calculation and kinetics calculation of critical stresses required for martensitic transformation, twinning, and dislocation slip. The content of martensite in the HR (the as‐cast sample hot rolled at 1173 K and air quenched) sample is decreased, whereas in the HRQ (the HR sample annealed at 1273 K for 2 h and water quenched) sample is increased. The content of martensite in the CR (the HRQ sample cold rolled with 40% deformation) sample is significantly increased, whereas in the CRQ (the CR sample annealed at 1173 K for 5 min and water quenched) sample is decreased. Thermodynamics and kinetics calculations show that the martensitic transformation is inhibited at high temperature due to its positive martensitic transformation free energy difference (Δ G γ → ε ), high stacking fault energy, and the highest critical stress required for martensitic transformation compared with twinning and dislocation slip. Martensitic transformation is promoted by deformation at low temperature due to its negative Δ G γ → ε, low stacking fault energy, and the lowest critical stress. Abstract : The characteristic of martensite transformation during deformation/heat treatment is analyzed. Transformation is inhibited at high temperature due to its positive martensite transformation free energy difference (Δ G γ → ε ), high stacking fault energy, and high critical stress for transformation. Transformation is promoted by deformation at low temperature due to its negative Δ G γ → ε, low stacking fault energy, and low critical stress.